2017
DOI: 10.1111/1556-4029.13604
|View full text |Cite
|
Sign up to set email alerts
|

The Appearance, Taste, and Concentrations of Zolpidem Dissolved in Still Water and Carbonated Beverages

Abstract: Zolpidem is a sedative that could be used to drug victims, but its suitability to dissolve in drinks is unknown. In this small study, we added either crushed or whole tablets of zolpidem hemitartrate to carbonated beverages or still water to observe how this affected the taste and appearance. Also, concentrations were measured by ultra-high performance liquid chromatography tandem mass spectrometry at different time intervals. Two crushed tablets (20 mg) in cider (250 mL) lead to a maximum concentration of 84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In a study investigated the solubility of crushed and whole zolpidem tablets in pure water, cider and mineral water, Heide et al used liquid chromatography-tandem mass spectrometry (LC-MS/MS) system and found the results within the LOD value with the linear range of the presented method. It is understood that the analysis method presented, according to these results, can be easily detect zolpidem in different matrices such as food and beverages [13].…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In a study investigated the solubility of crushed and whole zolpidem tablets in pure water, cider and mineral water, Heide et al used liquid chromatography-tandem mass spectrometry (LC-MS/MS) system and found the results within the LOD value with the linear range of the presented method. It is understood that the analysis method presented, according to these results, can be easily detect zolpidem in different matrices such as food and beverages [13].…”
Section: Resultsmentioning
confidence: 81%
“…Zolpidem, zopiclone and zaleplone, called Z-drugs, are commonly used as an alternative to benzodiazepines in the treatment of insomnia. Zolpidem is the most preferred Z-drugs by means of its minimal day after side effects [13]. In addition to the treatment of insomnia, it has anticonvulsant, anxiolytic and minor muscle relaxant properties [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, these drugs seem to have become more widespread than before and sometimes even cause death. 1–5 Blood is the primary biological fluid of choice for toxicology analysts to work in criminal cases; however, other matrices are often tested to either substantiate the concentrations found in blood or in instances of a limited sample. So sample pretreatment, including the extraction and purification of analytes, is one of the most important processes in the determination of trace-level drugs and metabolites in biological samples.…”
Section: Introductionmentioning
confidence: 99%